2009
DOI: 10.1016/j.vacuum.2009.01.072
|View full text |Cite
|
Sign up to set email alerts
|

Structures and properties of Ti alloys after double implantation

Abstract: -The paper presents new results on investigation of structure and physical-mechanical properties of near surface layers of titanium alloys after (W + , Mo + ) ion implantation and subsequent thermal annealing under 550 °C during 2 h. Using back scattering (RBS) of helium ions and protons, scanning electron microscopy (SEM) with microanalysis (EDS), (WDS), proton (ion) induced X-ray emission (PIXE), X-ray phase analysis (ERD) with a sliding beam geometry (0.5 °C), Mössbauer spectroscopy (MS), measurements of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…They validated the significance of the modified surface on their excellent performance in wear and corrosion testing. Pogrebnjak et al [ 23 ] demonstrated that the implantation of W and Mo ions, followed by annealing of Ti-6Al-4V surface, resulted in improved nano-hardness and wear resilience, due to the formation of nitrides, carbo-nitrides, and inter-metalloids. Man et.…”
Section: Introductionmentioning
confidence: 99%
“…They validated the significance of the modified surface on their excellent performance in wear and corrosion testing. Pogrebnjak et al [ 23 ] demonstrated that the implantation of W and Mo ions, followed by annealing of Ti-6Al-4V surface, resulted in improved nano-hardness and wear resilience, due to the formation of nitrides, carbo-nitrides, and inter-metalloids. Man et.…”
Section: Introductionmentioning
confidence: 99%
“…51 Chen and co-workers found that SNMS and XPS differentiated between the tribofilms created by different additives on aluminium surfaces. Pogrebnjak et al 52 investigated the near surface structure and properties of titanium alloys, after implantation of W and Mo ions. Composition was determined using SEM-EDX and PIXE.…”
Section: Non-ferrous Metals and Alloysmentioning
confidence: 99%
“…Furthermore, it has been reported in many cases that the irradiation of a material by two or more distinct types of ions (for example, gas and metal ions) results in more significant changes in the properties of the material [14,15]. Implanted elements such as Cr, Ti, and N can undergo different degrees of phase formation and microstructural change, as well as mechanical and chemical enhancements [16,17,18,19,20,21,22]. For instance, Pogrebnjak found that an increase in hardness and a reduction of wear in double-implanted Ti alloys was attributed to the formation of small dispersion nitride, carbonitride, and intermetalloid phases [17].…”
Section: Introductionmentioning
confidence: 99%
“…Implanted elements such as Cr, Ti, and N can undergo different degrees of phase formation and microstructural change, as well as mechanical and chemical enhancements [16,17,18,19,20,21,22]. For instance, Pogrebnjak found that an increase in hardness and a reduction of wear in double-implanted Ti alloys was attributed to the formation of small dispersion nitride, carbonitride, and intermetalloid phases [17]. Sudjatmoko highlighted that the optimum enhancement of hardness properties and wear resistance of Ti-6Al-4V alloy after nitrogen implantation was principally due to the formation of ceramic Ti 2 N and TiN phases [20].…”
Section: Introductionmentioning
confidence: 99%